ELABORATIVE INFERENCES - Iza Mikeleiz, Mauricio; Ezquerro, Jesús (Anales de Psicología / Annals of Psychology, 2000)
According to psychological experimentation, there is evidence of automatic elaborative inferential activity, as well as of incompleteness in backward inference making (anaphora, causal structuring). McKoon & Ratcliff (1992) have argued for a “minimalist” theory of inference in reading, contrasting it with “constructionist” theories, including theories based on mental or situation model. But, minimalism has mischaracterized text understanding, failing to notice that the extent to which an inferential activity is relevant (in focus) affects the speed and easiness of performing inferences, as it happens with anaphora resolution. Although a theory of discourse processing should be both constructionist and minimalist, we discuss the relationship between a computational theory of inference making and a description of the mechanisms underlying our inferential abilities.